2009
DOI: 10.1016/j.biomaterials.2008.09.026
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cytokine-associated responses to biomaterials

Abstract: Cytokines, chemokines, and growth factors were analyzed periodically over eight weeks from the wound exudate fluid surrounding biomaterials implanted subcutaneously within stainless steel mesh cages. TNF-α, MCP-1, MIP-1α, IL-2, IL-6, IL-1β, VEGF, IL-4, and IL-10 were measured from exudate samples collected from cages containing specimens of polyethylene (PE), polyurethane (PU), or organo-tin polyvinyl chloride (ot-PVC). Empty cages served as negative controls, and lipopolysaccharide (LPS) served as a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 33 publications
5
82
1
3
Order By: Relevance
“…To examine the response of the body after implantation of biomaterials, the in vivo determination of different cytokines has recently been used in several studies [8][9][10][11]. Furthermore, a recent study which found that variations in the genes of cytokines including IL-2 and IL-6 influence the severity of osteolysis in patients with total hip arthroplasty demonstrates the potential relevance of cytokines for implant-associated complications [12].…”
Section: Introductionmentioning
confidence: 98%
“…To examine the response of the body after implantation of biomaterials, the in vivo determination of different cytokines has recently been used in several studies [8][9][10][11]. Furthermore, a recent study which found that variations in the genes of cytokines including IL-2 and IL-6 influence the severity of osteolysis in patients with total hip arthroplasty demonstrates the potential relevance of cytokines for implant-associated complications [12].…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the composition of sealers, all materials might induce some signaling pathways stimulating the expression of pro inflammatory cytokines and prostaglandins that are involved in initiation of the inflammatory process and that may contribute to a sequence of healing events. 28,29 Many studies have shown that the inflammatory state produces an unfavorable environment for angiogenesis, cellular proliferation, and wound healing.…”
Section: Sealapexmentioning
confidence: 99%
“…However, the levels were independent of the chemical composition of the tested materials (polyethylene, organotin impregnated polyvinyl chloride and polyurethane). Most of the cytokines identified were pro-inflammatory/ anti-wound healing, and their concentrations in all of the cases tended to decrease over time [24]. The similar cytokine profiles induced by these materials suggest that similar tissue reactions, such as vascularization and fibrous tissue formation, occur in vivo with these chemically diverse, polymeric biomaterials.…”
Section: Discussionmentioning
confidence: 85%